Competitive intelligence and developing sustainable competitive advantage (2017)
Privatization, partial tariff liberalization and entrance of foreign insurance companies in Iranian market pose serious challenges to domestic insurance companies. This paper discusses competitive intelligence as a means of gaining competitive advantage for insurance companies and seeks to study its effects on creation of sustainable competitive advantage. A sample of 123 middle and senior managers working in Iran Insurance Company in Tehran were surveyed. Data were collected via questionnaire and analyzed using Structural Equation Model (SEM) in PLS software. Results showed that competitive intelligence had a positive effect on creation of competitive advantage based on two sets of process and contextual factors, with the former exerting greater effect in this regard. It was concluded that companies were required to gain competitive advantage by establishing a strategic unit to collect, analyze and share intelligent information derived from internal and external environment